A comparison of six major platelet functional tests to assess the impact of carbon nanomaterials on platelet function: A practical guide. Issue 2 (March 2014) - Laloy, Julie; Mullier, François; Alpan, Lutfiye; Mejia, Jorge; Lucas, Stéphane; Chatelain, Bernard; Toussaint, Olivier; Masereel, Bernard; Rolin, Stéphanie; Dogné, Jean-Michel
Abstract The study of the haemocompatibility of nanomaterials that could be in contact with blood (e.g. nanoparticle (NP)-based drug-delivery system) is of major importance. The primary objective of this study was to compare the ability of six platelet functional tests to assess the impact of NPs on platelet function. The secondary objective was to determine an accurate and reliable screening test to measure the potential impact of NPs on primary haemostasis whatever their physicochemical properties. Four types of carbon NPs (carbon black, fullerenes, single-walled carbon nanotubes and multi-walled carbon nanotubes) were investigated on six platelet function tests: light transmission aggregometry, whole-blood impedance aggregometry, platelet function analyser-100 (PFA-100®) and Cone-and-Plate(let) analyser (Impact-R®), transmission- and field emission gun scanning electron microscopy (FEG-SEM). We considered that Impact-R® supported by FEG-SEM is the reference method to investigate the potential impact of NPs on platelet function.